2018
DOI: 10.18553/jmcp.2017.17218
|View full text |Cite
|
Sign up to set email alerts
|

Slow Titration and Delayed Intensification of Basal Insulin Among Patients with Type 2 Diabetes

Abstract: This study was funded by Novo Nordisk. Mocarski, Guerrero, Langer, and Thorsted are employees and shareholders of Novo Nordisk. Yeaw, Divino, and DeKoven are employed by QuintilesIMS, which received remuneration from Novo Nordisk for work on this study. Study concept and design were contributed by Mocarski, DeKoven, Langer, and Thorsted. Yeaw took the lead in data collection, along with Divino and DeKoven. Data interpretation was performed by Yeaw, Divino, DeKoven, and Guerrero. The manuscript was written by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
(39 reference statements)
1
33
0
1
Order By: Relevance
“…In a recently published database analysis, it was observed that titration of basal insulin was characterized by substantial treatment inertia in the real world . This may be attributable to the reluctance of patients and physicians to titrate insulin for many reasons, including fear of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published database analysis, it was observed that titration of basal insulin was characterized by substantial treatment inertia in the real world . This may be attributable to the reluctance of patients and physicians to titrate insulin for many reasons, including fear of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…32 In a recently published database analysis, it was observed that titration of basal insulin was characterized by substantial treatment inertia in the real world. 33 This may be attributable to the reluctance of patients and physicians to titrate insulin for many reasons, including fear of hypoglycaemia. In the present study, continuation of sitagliptin when initiating and intensively titrating insulin glargine led to participants achieving greater glycaemic control and no evidence of an increased hypoglycaemic burden typically associated with intensifying insulin glargine.…”
Section: Discussionmentioning
confidence: 99%
“…2,14 An insulin dose of >0.4 IU/kg/d should be a signal to clinicians to start considering antidiabetic agents that better address PPG excursions, including prandial insulin, or oral or injectable incretin therapies, so that treatment intensification can be initiated before basal insulin doses exceed 0.5 IU/kg/d. 2,18 The limitations of the present study primarily relate to the fact that it is a post hoc analysis of pooled data from three studies not specifically designed to determine if there is a diminishing response to increasing basal insulin dose. Furthermore, specifying that participants required a background therapy of metformin and a sulphonylurea limited the number studies that could be included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Moreover, a significant proportion of people with diabetes are concerned about the risks of hypoglycaemia and potential weight gain associated with higher basal insulin doses. Early intensive glucose control is essential to prevent long-term micro-and macrovascular complications of type 2 diabetes, 17 but many people with type 2 diabetes do not achieve their HbA1c targets on basal insulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation